Linking Water Access and Education in the Sustainable Development Goals in Sub-Saharan Africa - Fils, Le Roi Nso (Asian Journal of Empirical Research, 2021)
Despite the growing literature on water access, little is known about the effect of water access on education, particularly in sub-Saharan African countries. The aim of this paper is to fill this gap by assessing how water access affects education in 23 sub-Saharan African countries over the period 2000-2018. To carry out our investigation, we used the Generalized Moments Methods (GMM). The results show that there is a negative relationship between water access and education. Furthermore, parliament women and government effectiveness play an important role in mitigating the negative impact of water access on education. Finally, the positive association between water access and education in sub-Saharan Africa is conditioned by the achievement of a certain threshold of parliament women and government effectiveness.